2019
DOI: 10.1101/621094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time elapsed between Zika and dengue virus infections affects antibody and T cell responses

Abstract: 34The role of Zika virus (ZIKV) immunity on subsequent dengue virus (DENV) infections is 35 relevant to anticipate the dynamics of forthcoming DENV epidemics in areas with previous ZIKV 36 exposure. We study the effect of ZIKV infection with various strains on subsequent DENV 37 immune response after 10 and 2 months of ZIKV infection in rhesus macaques. Our results 38show that a subsequent DENV infection in animals with early-and middle-convalescent periods 39 to ZIKV do not promote an increase in DENV viremia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 96 publications
(121 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, the dispersal velocity of these persistent DENV lineages peaked in 2016 and slowed with the decline of Zika and dengue in 2017. Together, our results indicate that DENV established cryptic transmission for more than five years before causing outbreaks in 2019, perhaps due to waning cross-protection provided by existing DENV and/or ZIKV population immunity 14,26 , a scenario that may have occurred across the Americas.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the dispersal velocity of these persistent DENV lineages peaked in 2016 and slowed with the decline of Zika and dengue in 2017. Together, our results indicate that DENV established cryptic transmission for more than five years before causing outbreaks in 2019, perhaps due to waning cross-protection provided by existing DENV and/or ZIKV population immunity 14,26 , a scenario that may have occurred across the Americas.…”
Section: Introductionmentioning
confidence: 74%
“…This reduction in susceptibility in 2017 and 2018 was likely a result of high DENV transmission over several preceding years, which may have provided some within and between DENV serotype protection (though we do not have sufficient data on serotypes to analyze). Based on this analysis, however, we cannot exclude a possible role for other factors, such as cross-protection conferred by ZIKV infection 14,26 , as also contributing to a reduction in dengue incidence in those years.…”
Section: Annual Dengue Virus Force Of Infectionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lastly, using polyclonal sera from individuals who had naturally acquired ZIKV infection, we demonstrated that the antigens expressed by the hAd5-ZKV vaccine are recognized by the ZIKV-driven human polyclonal antibody response. Based upon our prior work as well as work by others, it can be said that the antigen-specific T cell and antibody responses can protect against ZIKV disease [ 19 , 21 , 22 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current data from both naturally acquired human infection and mouse models of ZIKV disease indicate that protection from disease is multi-faceted (reviewed in [ 14 , 15 , 16 , 17 , 18 ]). Both small and large animal models of ZIKV infection have demonstrated that the Zika-specific CD8 + and CD4 + T cell response is necessary and sufficient to protect against a lethal ZIKV challenge [ 19 , 20 , 21 , 22 ]. As has been demonstrated previously for multiple flavivirus infections [ 23 , 24 , 25 ], ZIKV-specific polyclonal and monoclonal neutralizing antibody responses can protect mice and nonhuman primates from mortality and severe disease.…”
Section: Introductionmentioning
confidence: 99%